Antidiabetic effects of Centratherum anthelminticum seeds methanolic fraction on pancreatic cells,ß-TC6 and its alleviating role in type 2 diabetic rats - Arya, Aditya; Looi, C.Y.; Cheah, S.C.; Mustafa, Mohd Rais (Elsevier, 2012)
Ethnopharmacological relevance:Seeds of Centratherum anthelminticum (Asteraceae)have been popularly used in Ayurvedic medicine to treat diabetes and skin disorders.Folk medicine from Rayalaseema(Andhra Pradesh,India)reported wide spread usage in diabetes. Aim of the study:To investigate the hypoglycemic properties and mechanism of the me than olic fraction of Centratherum anthelminticum seeds(CAMFs)on mouse ß-TC6 pancreatic cell line and streptozotocin (STZ)induced diabetic rat models. Materials and Methods:We investigated the crude methanolic fraction of Centratherum an thelminticum seeds(CAMFs)on ß-TC6 cellline and confirmed its effects on type 1 and type 2 diabetic rats to understand its mechanism in managing diabetes mellitus.(CAMFs) was initially tested on ß-TC6 cells for cytotoxicity, 2 NBDG glucose uptake,insulin secretion and glucose transporter (GLUT1,2and4)protein expression.Furthermore,streptozotocin(STZ)–induced type 1 diabetic and STZ-nicotinamide–induced type2 diabetic rats were in traperitoneally (i.p)injected or administered orally with CAMFs daily for 28days.The effect of CAMFs on blood glucose and insulin levels was subsequently evaluated.